AVALIAÇÃO DO EFEITO NEUROPROTETOR DA NARINGINA E NARINGENINA NANOENCAPSULADAS EM MODELO DE DEMÊNCIA INDUZIDA POR ESTREPTOZOTOCINA EM CAMUNDONGOS - Ferreira, Carla Fontoura (2017)
Reactive species (ERs) and oxidative stress contribute to the pathophysiology of several diseases including dementia. An innovative alternative for protecting organs such as the brain is the use of antioxidant-like flavonoids such as naringin and naringenin. However, these two compounds have low bioavailability when administered orally. An alternative to overcome this limitation is the use of nanocarriers, such as nanocapsules (NC). Therefore, the present study aimed to evaluate the neuroprotective effect of naringin and naringenin in a model of streptozotocin (STZ) -induced dementia in mice. The profile of drug release from in vitro suspensions was evaluated as well as the effects of nanoencapsulated drugs on cell viability with Vero cell line. In addition, the involvement of oxidative stress in the brain tissue of mice was verified. Naringin and naringenin NC had acid pH, particle diameter less than 95 nm, polydispersity index (IPD) of less than 0.2. The zeta potential was negative, between -12.46 and -17.6 mV, and the encapsulation efficiency was 93% for naringin and 95% for naringenin. For the study of the release profile, the dialysis technique was used, with 46.5% of naringin and 6.9% of naringenin being released in the medium, in a period of 9h. The results of the cell viability assay showed that the NC suspensions caused a reduction in cell viability of Vero cells at concentrations of 5, 50 and 500 μg / ml when compared to the control at the 24 and 72h incubation periods. For in vivo evaluation of neuroprotection the mice were pretreated for 15 days by oral (vo) with the suspension of white nanocapsules (NB), NC containing the mixture naringin and naringenin (N-NANG), suspension of naringin and naringenin in the form Free (NANG) and vehicle (Sham) at dose 10 mg / kg body weight. Subsequently, stereotactic surgery was performed for intracerebroventricular (i.c.v) infusion of STZ or FAC (cerebral artificial fluid). Behavioral tasks were then initiated. In the open field task the locomotor activity differed in the test section in the NB + STZ group evidenced by a hyperlocomotion between the mice of this experimental group. For exploratory activity there was no significant difference between groups. In the evaluation of the short-term memory in the task of object recognition the animals treated with N-NANG did not recognize the new object. For the long-term memory there was learning only for the mice treated with NB. The mice treated with NB + STZ had memory impairment assessed in the task of inhibitory avoidance, and pre-treatment with N-NANG prevented this effect. In the evaluation of the anti-depressive and anxiolytic-type effects, it was observed that the NNANG + STZ induced greater body activity in the twist parameter in the tail suspension task and in the high "zero" labyrinth there was an increase in the number of spies Relative to the free drug. Regarding the levels of brain antioxidants, there were no changes in the levels of reduced glutathione (GSH) and catalase activity (CAT). The NB + STZ group significantly increased levels of brain lipid peroxidation of thiobarbituric acid reactive species (TBA). N-NANG administration reduced the peroxidation induced by STZ. Thus, it can be concluded that the CNs present characteristics suitable for oral administration. In vivo studies demonstrate that pre-treatment with naringin and naringenin NC was preventative and able to reverse memory deficits, type-depressive and anxiolytic behavior caused by STZ in mice. However, this preventive effect was not observed with the flavonoids in the free form.